Cohort Analysis: Dropout, Lag and Terminal Efficiency in the Bachelor of Medicina and Surgery of the University of Medical Sciences - Juan Carlos Vanegas-Pissa; Hilda Sancho-Ugalde (Revista Electrónica Educare)
This study aims to analyze the institutional completion rates, the dropout rates, the student lag, and the average number of years to successfully complete the degree in Medicine and Surgery. The population consists of four cohorts: from I-2008(n=252), II-2008 (n= 142), I 2009 (n= 214) and II- 2009 (n= 144). The data come from the institutional database “AVATAR”, fed by the Registration Department, with socio-demographic variables and grades by subject and academic period, which are automatically uploaded to the system and corroborated with the reports delivered by each teacher. To analyze the data we used the Stata v-14 package, the survival models (duration models) and a Cox regression model was adjusted. The completion rate is 29,9%, with a duration of 11-13 semesters (5½ 6½ years), 12,8% prolong their studies up to one more semester. The average dropout rate of the cohorts was 55,2%, occurring during the first six semesters of the career. An important cause of dropout is the multiple repetition of Basic Science courses that gives a lag of 14,9%. We recommended to carry out studies that clarify the causes of these results and allow the renovation of didactic methods, curricular redesign, and study methods to overcome these problems.